Embedded Linux : hardware, software, and interfacing - Hollabaugh, Craig (Addison-Wesley, 2002)
Embedded Linux will help the user: select an Embedded Linux platform based on hardware requirements; build and boot a custom Linux kernel for the platform; remote debug programs running on the platform using GNU tools; connect data acquisition and control electronics/peripherals using the platform's serial, parallel, USB, I/O port and I2C interfaces; interface the peripherals to the kernel and applications using modules; collect, control, store and present data via open source protocols and applications; and analyze Embedded Linux vendor product offerings.